Perancangan Aplikasi Management Usaha Pemakaman Berbasis Web Pada Lamtama Funeral Service - Saoloan Natan Yoel Silalahi; Tony Tony (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Lamtama Funeral Service is a service business based in Palembang that has been relying on basic communication tools such as text and calls to manage its operations. The absence of a structured digital system poses challenges in data management, service scheduling, and customer coordination, often leading to inefficiencies and risks of human error in service delivery. This study aims to design a web-based funeral service management application tailored to the operational needs of Lamtama Funeral Service. The system is expected to digitize and streamline key processes such as deceased data management, funeral scheduling, service package administration, document archiving, payment confirmation, and online consultation for clients. The development process adopts the Waterfall methodology, which provides a systematic and sequential approach through stages of requirement analysis, system design, implementation, testing, and maintenance. The result of this research is a web application prototype that offers a more organized and accessible platform for Lamtama staff, thereby improving service efficiency, data accuracy, and customer satisfaction.